Possibilities of usefulness of Complex network of Grief Theory as reflective tool for assessment (Paliativní medicína, 2022)
The article is a case study of the initial assessment sessions with the client Anna (anonymized), viewed through the lens of Grief as a complex network theory. The strategic nodes of Anna's form of grieving and their connections (edges) are described, as well as possible working hypotheses in terms of further work with the client.
Keywords: Complex network of Grief theory; Case report; Methods of interventions; Grief; Mourning; Bereavement; Assessment